Exploring the Impact of Dry Cupping and Wet Cupping Therapy on Haemoglobin Levels During Menstruation among Adolescent Females: A Preliminary Comparative Study - Setyawan, Aris; Saifudin, I Made Moh. Yanuar (Indonesian Journal of Global Health Research, 2023)
Adolescence is a critical phase of transition from childhood to adulthood, characterized by various reproductive health challenges. Anaemia is a prevalent problem, with approximately 10% of women experiencing significant haemoglobin loss through menstrual bleeding. Non-pharmacological approaches, including cupping therapy, have shown promise in managing anaemia and menstrual issues. This study aimed to compare and evaluate the effectiveness of dry cupping therapy and wet cupping therapy in improving haemoglobin levels during menstruation among late adolescents. A quasi-experiment with a pre-post test without control group design was conducted. The sample consisted of 70 respondents, with 35 participants in the dry cupping group and 35 participants in the cpc-wct cupping group, selected using purposive sampling. The data were analyzed using the paired t-test and independent t-test. Both the dry cupping group (t=-4.896, p<0.001) and the cpc-wct group (t=-12.727, p<0.001) experienced a significant increase in haemoglobin level after the implementation of cupping therapy. However, there was no statistical significant difference in haemoglobin levels between groups after the intervention (t= 0.425, p=0.534). This suggests that the outcomes or measured variables did not significantly differ between the two cupping groups following the intervention. Cupping therapy, whether applied through cpc-wct or dry techniques, has the potential to enhance haemoglobin levels in adolescents during menstruation. Cpc-wct cupping, in particular, is perceived as a more effective method compared to dry cupping. Consequently, both cpc-wct and dry cupping can be considered as viable alternative interventions for raising haemoglobin levels in adolescents during menstruation.